Consumption of Sugar-Sweetened Beverages and Its Potential Health Implications in Indonesia - Sartika, Ratu Ayu D; Atmarita, Atmarita; Duki, M. I Zulkarnain; Bardosono, Saptawati; Wibowo, Lindawati; Lukito, Widjaja (Kesmas, 2022)
The broad availability of sugar-sweetened beverages (SSBs) in the Indonesian market is increasing consumption. It, combined with escalating incidence and prevalence of diabetes and related non-communicable diseases (NCDs), and the ongoing debate on policies, has called for a comprehensive review as described in this study. Data was compiled from various sources but mainly gathered from the reported or published documents because of no direct access to the necessary data set. The lack of studies that assessed the direct relationship between SSB consumption and health outcomes in the Indonesian context also became a strong reason for the preparation of this review to highlight important points for further research, academic reviews, and debates on empiric policies to control sugar consumption at the population level. Sociocultural factors were an apparent and crucial determinant of the sweetness preferences of mainstream Indonesians. They were not capitalized in the available documents and should be embraced in future health promotional measures. Given the high contribution of carbohydrates and sugar to total energy intake in the Indonesian diet, it is pertinent to control the increasing trend of SSBs consumption through interventions on both the supply and demand sides.